The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/8302674
|View full text |Cite|
|
Sign up to set email alerts
|

Machine Learning Techniques for Human Age and Gender Identification Based on Teeth X-Ray Images

Abstract: The use of digital medical images is increasing with advanced computational power that has immensely contributed to developing more sophisticated machine learning techniques. Determination of age and gender of individuals was manually performed by forensic experts by their professional skills, which may take a few days to generate results. A fully automated system was developed that identifies the gender of humans and age based on digital images of teeth. Since teeth are a strong and unique part of the human b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Previous studies have shown that artificial intelligence or machine learning algorithms can improve sex determination accuracy and lead to better results 4 . These methods have become increasingly popular in recent years because of their classification capacity and lack of strict criteria and assumptions, such as discriminant function analysis or regression analysis 48–52 . In the current study, machine learning algorithms were used to determine whether they could provide an improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that artificial intelligence or machine learning algorithms can improve sex determination accuracy and lead to better results 4 . These methods have become increasingly popular in recent years because of their classification capacity and lack of strict criteria and assumptions, such as discriminant function analysis or regression analysis 48–52 . In the current study, machine learning algorithms were used to determine whether they could provide an improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed technique produced good results with a mean absolute error of 5.15 years and a concordance correlation value of 0.80. In another research [19], multiclass Support Vector Machine (SVM) for age estimation and a Library for Support Vector Machines (LIBSVM) for the prediction of gender is used. A total of 1142 X-Rays of teeth were used for research and experiments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although, the results are reasonable, however, 814 scans could not ensure robustness of the model. In the research [19], SVM has been used for age and gender estimation. Model has been evaluated on a total of 1142 images, with achieved accuracy as 96%.…”
Section: Comparison With the State-of-the-art Studiesmentioning
confidence: 99%
“…Tasks in speech recognition or image recognition can take minutes rather than hours compared with manual identification by human experts [ 18 ]. Deep Learning’s application in forensic medicine has been explored over recent years due to its advantages of accuracy and precision in age and gender estimation [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study utilized X–ray images of teeth along with Machine Learning techniques to achieve 97% accuracy in age estimation, which implies that Machine Learning can be applied effectively in forensic investigations to obtain accurate and quick results [ 19 ]. Gender determination on panoramic radiographs using neural networks also exhibited good gender prediction compared with other methods, such as logistic and discriminant analysis [ 20 ].…”
Section: Introductionmentioning
confidence: 99%